Optimization of Air Plasma Reconversion of UF[6] to UO[2] based on Thermodynamic Calculations; AIP Conference Proceedings; Vol. 1938 : Isotopes: Technologies, Materials and Application (ITMA-2017) - Tundeshev N. V. Nikolay Vladislavovich (2018, 2018)
Title screen